Exploring the gene regulatory dynamics of the maturing human brain - Fillmore, Stephanie (Department of Human Biology, 2023)
The human brain develops gradually overtime where distinct molecular profiles are established in the embryo. These molecular profiles continue to change through aging and in response to environmental factors. The complexity and dynamics of gene expression and regulation at the cell type-specific level are still poorly understood, especially during the process of brain maturation. The overall aim of this project was to obtain a better understanding of how the brain cell atlas changes over time by contributing to the current brain cell atlas with pediatric single cell data. Bio-banked pediatric and adult brain tissue samples, obtained during surgery to treat epilepsy, were used to optimise and generate a nuclei isolation protocol. Single nuclei RNA-seq (snRNA-seq) libraries were generated using the 10x Genomics Platform. snRNA-seq datasets were then sequenced and analysed using bioinformatics tools, including Cell Ranger and Seurat. The major cell types in the pediatric brain were identified, including the genes being expressed by these cell types. In addition, a pilot differential expression analysis study was conducted between snRNA-seq libraries from the temporal and frontal lobes. Furthermore, Assays for Transposase Accessible Chromatin (ATAC-seq) was performed on pediatric and adult tissue and bulk ATAC-seq libraries were successfully generated. A consensus list of putative enhancers and promoters was generated after testing several bioinformatic pipelines. Differential accessibility analysis was performed on the bulk ATAC-seq datasets and the promoters or enhancers that are being dynamically used over the course of brain development, were also identified. Ultimately, with these findings and with the generation of optimised protocols, this study has contributed to our understanding of gene expression and gene regulation of brain maturation.